2021
DOI: 10.3390/plants10010180
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and Sulfur Coordinately Modulate the Antioxidant System and ABA Accumulation in Mustard Plants under Salt Stress

Abstract: This study explored the interactive effect of ethephon (2-chloroethyl phosphonic acid; an ethylene source) and sulfur (S) in regulating the antioxidant system and ABA content and in maintaining stomatal responses, chloroplast structure, and photosynthetic performance of mustard plants (Brassica juncea L. Czern.) grown under 100 mM NaCl stress. The treatment of ethephon (200 µL L−1) and S (200 mg S kg−1 soil) together markedly improved the activity of enzymatic and non-enzymatic components of the ascorbate-glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 97 publications
1
74
0
Order By: Relevance
“…It may be said that there is ethylene signaling in guard cells to induce changes in abscisic acid (ABA) level for stomatal movement in the presence of Glu under salt stress. Fatma et al 61 showed ethylene in the presence of sulphur induced ABA changes in guard cell, leading to increased stomatal conductance and structure and efficiency of photosynthetic apparatus in Brassica juncea under salt stress. The application of ethylene increased GSH content that led to cellular redox homeostasis and controlled stomatal movement.…”
Section: Discussionmentioning
confidence: 99%
“…It may be said that there is ethylene signaling in guard cells to induce changes in abscisic acid (ABA) level for stomatal movement in the presence of Glu under salt stress. Fatma et al 61 showed ethylene in the presence of sulphur induced ABA changes in guard cell, leading to increased stomatal conductance and structure and efficiency of photosynthetic apparatus in Brassica juncea under salt stress. The application of ethylene increased GSH content that led to cellular redox homeostasis and controlled stomatal movement.…”
Section: Discussionmentioning
confidence: 99%
“…The content of ABA was estimated by adopting the method of Hung and Kao (2003) with small modi cations. The details are given in Fatma et al (2021) and provided in the Supplementary File 1.…”
Section: Abscisic Acid Determinationmentioning
confidence: 99%
“…Similarly, ethylene biosynthesis is stimulated under drought stress (Apelbaum and Yang 1981;Morgan and Drew 1997;Nazar et al 2015); however it is stress ethylene that has be brought to an optimum level to initiate maximum utilization of available resource. Ethylene has been found to play a role in the auxininduced opening of stomata in Vicia faba (Merrritt et al 2001) and in modulation of stomatal closure induced by ABA (Fatma et al 2021). It has been shown that using ethephon (an ethylene-releasing compound) enhanced stomatal conductance, resulting in an increase in photosynthesis (Iqbal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene evolution in leaves was assessed using gas chromatograph by the process de ned previously by Fatma et al (2021).…”
Section: Ethylene Evolutionmentioning
confidence: 99%
“…Sulfur is a major constituent of methionine (Met) and cysteine (Cys), Fe-S clusters, sulfolipids, S-methylmethionine (SMM), S-adenosylmethionine (SAM), glucosinolates, vitamins (biotin and thiamine), coenzyme A, thioredoxin system and GSH, a major antioxidant metabolite and non-protein thiol (Fatma et al 2013;Anjum et al 2015). Applied S improved the photosynthetic capacity of the plants in salt stress by improving the cellular GSH level, modulating the major components of the ascorbate-glutathione (AsA-GSH) cycle, restricting ROS formation, and thus, minimizing oxidative stress and its consequences (Fatma et al 2021).…”
Section: Introductionmentioning
confidence: 99%